Frailty indices predict mortality, complications and functional improvements in supratentorial meningioma patients over 80 years of age - Schwartz, Christoph; Ueberschaer, Moritz F.; Rautalin, Ilari; Grauvogel, Jürgen; Bissolo, Marco; Masalha, Waseem; Steiert, Christine; Schnell, Oliver; Beck, Jürgen; Ebel, Florian; Bervini, David; Raabe, Andreas; et al. (Journal of Neuro-Oncology, 2024)
Purpose: To assess whether the Modified 5 (mFI-5) and 11 (mFI-11) Factor Frailty Indices associate with postoperative mortality, complications, and functional benefit in supratentorial meningioma patients aged over 80 years. Methods: Baseline characteristics were collected from eight centers. Based on the patients’ preoperative status and comorbidities, frailty was assessed by the mFI-5 and mFI-11. The collected scores were categorized as “robust (mFI=0)”, “pre-frail (mFI=1)”, “frail (mFI=2)”, and “significantly frail (mFI≥3)”. Outcome was assessed by the Karnofsky Performance Scale (KPS); functional benefit was defined as improved KPS score. Additionally, we evaluated the patients’ functional independence (KPS≥70) after surgery. Results: The study population consisted of 262 patients (median age 83 years) with a median preoperative KPS of 70 (range 20 to 100). The 90-day and 1-year mortality were 9.0% and 13.2%; we recorded surgery-associated complications in 111 (42.4%) patients. At last follow-up within the postoperative first year, 101 (38.5%) patients showed an improved KPS, and 183 (69.8%) either gained or maintained functional independence. “Severely frail” patients were at an increased risk of death at 90 days (OR 16.3 (CI95% 1.7-158.7)) and one year (OR 11.7 (CI95% 1.9-71.7)); nine (42.9%) of severely frail patients died within the first year after surgery. The “severely frail” cohort had increased odds of suffering from surgery-associated complications (OR 3.9 (CI 95%) 1.3-11.3)), but also had a high chance for postoperative functional improvements by KPS≥20 (OR 6.6 (CI95% 1.2-36.2)). Conclusion: The mFI-5 and mFI-11 associate with postoperative mortality, complications, and functional benefit. Even though “severely frail” patients had the highest risk morbidity and mortality, they had the highest chance for functional improvement.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Elderly; Functional outcome; Meningioma; Modified 5 (mFI-5) and 11 (mFI-11) Factor Frailty Indices; Mortality